Electoral Accessibility Reform for Persons with Disabilities - Rahim, Erman I.; Piyo, Sofyan; Komendangi, Rivanka Amelia Nursyahbani (Fakultas Hukum Universitas Islam Jakarta, 2025)
Political participation of persons with disabilities in electoral processes remains constrained by structural barriers despite constitutional guarantees and international human rights commitments. This study examines the need for electoral accessibility reform by employing the concepts of accessibility and reasonable accommodation as normative and philosophical foundations. The research adopts a normative legal method with conceptual and statutory approaches. The findings indicate that while Indonesia’s legal framework formally recognizes accessibility and reasonable accommodation, implementation gaps persist, particularly in relation to physical infrastructure, electoral information, and socio-cultural practices. Drawing on distributive justice and principles protecting vulnerable groups, the study argues that accessibility should be understood as a substantive equality requirement rather than merely a technical administrative measure. It concludes that electoral reform should prioritize universal accessibility standards and proportionate accommodation mechanisms to ensure equal political participation of persons with disabilities within Indonesia’s democratic framework.